THE BEECH FOREST VEGETATION OF THE CEROVÁ VRCHOVINA MTS. (SOUTHERN SLOVAKIA) - Ujházy, Karol; Hrivnák, Richard; Belanová, Eva; Benčatová, Blažena (Hacquetia, 2015)
Field phytosociological research of the Fagus sylvatica dominated forests in the volcanic Cerová vrchovina Mts. was carried out in 2001. Standard methods of the Zürich-Montpellier approach were applied. Tabular synthesis with numerical divisive classification (TWINSPAN) and indirect gradient analysis (PCA) were used to differentiate particular communities. Within the Fagion alliance, four associations were recognized: Carici pilosae-Fagetum, Dentario bulbiferae-Fagetum, Melico-Fagetum and Asperulo-Fagetum. Four different plant communities of the Tilio-Acerion alliance were detected: Roso pendulinae-Tilietum cordatae, Mercurialis perennis-Fagus sylvatica community, Athyrium filix-femina-Fagus sylvatica community and Dryopteris filix-mas-Fagus sylvatica community. Semioligotrophic communities were classified as Luzulo-Fagetum within the Luzulo-Fagion alliance. Influences of several ecological factors on species composition are discussed. The type of relief, stoniness and humus content of topsoil seem to play the most important role.